Integrated biomaterials for biomedical technology - Ramalingam, Murugan; Tiwari, Ashutosh; Ramakrishna, Seeram; Kobayashi, Hisatoshi (Wiley ; Scrivener., 2012)
"The book provides all the important aspects dealing with the basic science involved in materials in biomedical technology, especially structure and properties, techniques and technological innovations in material processing and characterizations, as well as the applications"--Resumé vydavatele
Keywords: biomedicínské inženýrství; biologické materiály; biokompatibilita; biomedical engineering; biological materials; biocompatibility; kolektivní monografie; elektronické knihy; collective monographs; electronic books